Development of Kinemaster-Based Animated Video Media to Improve The Mufrodat of Class IV Students of Madrasah Ibtidaiyah - Khairunnisa, Fitri; Koderi, Koderi; Erlina, Erlina (Universitas Ahmad Dahlan, 2023)
This study is a research and development (R&D) investigation employing the ADDIE development model, a model devised by Robert Maribel that comprises five stages: Analysis, Design, Development, Implementation, and Evaluation. The research focuses on a fourth-grade class at MIN 5 Sukarame, comprising 25 students—13 male and 12 female. The validators for this study include subject matter experts and media experts. The data collection method involves pre-test and post-test data, and the T-test is employed for statistical analysis. The findings of this research are as follows: (1) The process of creating Kinemaster-based animated video media to enhance students' comprehension, (2) The developed media is highly acceptable, with material experts giving it a 93% approval rating and media experts rating it at 96.25%. The product's effectiveness is evident in the significant difference in learning outcomes, reaching 38.75. The T-test analysis yields t0 = 62.5, which is greater than the t-table value of 2.093. In conclusion, the Kinemaster-based animated video media for enhancing students' understanding of Arabic is deemed highly acceptable and effective.